Investigation of meteoric water and parent fluid mixing in a two-phase geothermal reservoir system using strontium isotope analysis: A case study from Southern Bandung, West Java, Indonesia. (July 2021) - Shoedarto, Riostantieka Mayandari; Tada, Yohei; Kashiwaya, Koki; Koike, Katsuaki; Iskandar, Irwan; Malik, Dwiyogarani; Bratakusuma, Boyke
Highlights: Water-rock interaction processes based on δ 18 O are verified from 87 Sr/ 86 Sr. Recharge mechanism is revealed by δ 18 O, Sr concentration, and 87 Sr/ 86 Sr analyses. Interaction between shallow and deep groundwater was elucidated. Three aquifers are identified to host hydrothermal circulation from 87 Sr/ 86 Sr. Abstract: Determinations of the recharge area and recharge mechanism in geothermal systems are essential for reservoir management and a sustainable resource use. To address this problem, studies aplenty have aimed to identify the recharge elevation using stable water isotopes, δ 2 H and δ 18 O. Nevertheless, the physical and chemical processes involved in the generation of a reservoir fluid from a deeply infiltrated recharge flow remain poorly understood. This study aims to clarify this process using strontium (Sr) concentrations and isotope composition from water and well rock samples by selecting a geothermal field with a two-phase reservoir system in Southern Bandung, West Java, Indonesia. The water samples are characterized by variable Sr isotopic compositions ( 87 Sr/ 86 Sr) (0.70450–0.70725) and low Sr concentrations (0.01–0.72 ppm). The 87 Sr/ 86 Sr of the well rocks is also variable (0.70400–0.70827) with particularly high Sr concentrations (9.1–53 ppm). Three types of domain that are the combinations of the reservoir fluid mixing with groundwater are identified. The first two types are shallow and deep groundwater composed of 90 % meteoric water and 10 % upflow fluids with Sr concentration 0.01 to 0.11 ppm and the 87 Sr/ 86 Sr from 0.7055 to 0.70725. The shallow groundwater may possibly carry a 87 Sr/ 86 Sr anomaly (higher than 87 Sr/ 86 Sr of plagioclase: 0.7065) from the anthropogenic activities through the pathways created by the intersection of the NW-SE and NE-SW inferred regional faults in the west part of the field, hosted by the Wayang Windu Formation. The deep groundwater type is also a mixture of 10 % parent fluid hosted by the deeper aquifer rocks Malabar Formation, with lower strontium isotopes ratio than the first aquifer ( 87 Sr/ 86 Sr 0.7045–0.7055). The third groundwater refers to the perched aquifer with mixture of 30 %–70 % parent fluid that has undergone condensation and mixing processes in Pangalengan Formation ( 87 Sr/ 86 Sr 0.70452–0.7052). This groundwater is thought to be the source of mostly hot springs in the study area.